Growth, bone maturation and ovarian size in girls with early and fast puberty (EFP) and effects of three years treatment with GnRH analogue (GnRHa) : Early and fast puberty (EFP) and GnRH analogue (GnRHa) treatment - Alaaraj, Nada; Soliman, Ashraf T; De Sanctis, Vincenzo; Hamed, Noor; Alyafai, Fawziya; Ahmed , Shayma; Khalil, Ahmed; Bedair, Elsaid; Elawwa, Ahmed (Acta Biomedica Atenei Parmensis, 2022)
Introduction: Early puberty (EP) in girls is defined as the onset of thelarche that begins after 6 years and before 8 years and/or acceleration in the tempo of pubertal development. The stage of puberty and the ovarian volume at presentation and the effect of treatment with GnRH analogue (GnRHa) on final adult height are still debated. Patients and methods: We analyzed the data of 22 girls, who presented early and fast puberty (FEP). The clinical stage of puberty, hormonal levels and the ovarian volume (OV) (measured by ovarian ultra-sonography) at presentation were studied. We recorded the effects of 3 years treatment with GnRHa on their growth in relation to their mid parental height, pubertal progression, and bone maturation. Results and conclusion: GnRHa therapy decreased the fast progress of puberty, skeletal maturation, and GV/year. It was successful in increasing the predicted final adult height comparable to or surpassing their mid-parenteral height. A larger OV at presentation was associated with reduced Ht-SDS after 3 years of GnRHa treatment. Clearly, a definitive evaluation of the efficacy of GnRHa as treatment for EFP in girls will require expanded and concerted studies.